Assessment of timing and performance based on trajectories from low-cost GPS/INS positioning - Waegli, A.; Meyer, F.; Ducret, S.; Skaloud, J.; Pesty, R. (Science and Skiing IV, 2008)
INTRODUCTION: Traditionally, development and testing of materials or equipment has been based on repeated measurements with resources including timing cells or wind tunnels. Similarly, the analysis of athletes' performance has relied on techniques such as measuring race segments (chronometry) and video recordings. These methods, however, appear vulnerable to changing meteorological conditions and the difficulty of replicating the posture and movements of test subjects from one trial to the next. Furthermore, chronometry has a discrete character while researchers, coaches, and athletes are interested in observing certain phenomena continuously. Satellite-based positioning offers continuous observation of the athletes' trajectory and velocity and has already proven its effectiveness in many sports, including skiing (Waegli and Skaloud, Spring 2007). However, the fluctuation in accuracy often discouraged the regular employment of the technology. Therefore, quality indicators are introduced in order to qualify the statistical relevance of the satellite data.